Periodontal status and treatment needs among Indian estate population - Ali, T.T.; Razak, I.A.; Zain, R.B. (1999)
The aim of this study was to determine the periodontal status and treatment needs among the Indian estate population. The Community Periodontal Index of Treatment Needs was used to obtained clinical data on 208 Indian subjects residing in three estates in the state of Selangor. The prevalence of periodontal disease among the subjects was 100. Less than 1 of the subjects had bleeding on probing as the highest CPITN score. About 97 of the subjects showed evidence of periodontal pocket of 4mm or more. Of these, half showed pocketing of 6mm or more. No statistically significant difference (p> 0.05) was observed between males and females in terms of the most severe periodontal conditions encountered. About 2.5, 1.6 and 0.9 sextants were involved with pocketing of 4-5mm, calculus and pocketing of 6mm or more respectively. Again this pattern of sextants involvement shows no significant difference by gender (p>0.05). All subjects required oral hygiene instruction and 97.4 required scaling. Complex periodontal care was required by 48.7 of the subjects. The findings of this study indicate an urgent need for an oral health promotion programme to be instituted aimed at the prevention of periodontal disease and the utilization of appropriate manpower for the control and management of the existing disease in the Indian estate population.